Evaluation of techniques for the detection of Karnal bunt (Neovossia indica) of wheat (Triticum aestivum) - VARSHNEY, J L (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1996-98 to compare the merits of different techniques for the detection of Karnal bunt of wheat (Triticum aestivum L. emend. Fiori & Paol.). Karnal bunt of wheat caused by Neovossia indica (Mitra) Mundkur is a high risk disease of national and international importance. The infection can be examined by visual inspection of dry seeds, washing test and seed soak method. Visual inspection of dry seeds and seed soak method help to estimate the number of infected seeds in a seed lot. However, in view of the nature, establishment and spread of the disease, detection of even a single teliospore of the pathogen carried in any form is significant. Seed soak method is uneconomical, time-consuming, cumbersome, unreliable and quantitatively inaccurate because many of the teliospores are lost during decantation and drying. Nevertheless, at times the number of infected seeds decrease because many of the most severely infected seeds get fragmented and subsequently lost during decantation. However, teliospores are reliably detected by washing test which is easy, rapid, less time consuming and quantitatively accurate and, therefore, it has been adopted by several countries.